A New Hybrid Image Encryption Technique Using Lorenz Chaotic System and Simulated Kalman Filter (SKF) Algorithm - Nurnajmin Qasrina Ann, .; Pebrianti, Dwi; Mohammad Fadhil, Abas; Bayuaji, Luhur (Springer, Singapore, 2022)
Nowadays, encryption is one of the most popular and effective security methods used by company and organizations. A new hybrid technique, Lorenz chaotic system and an optimization algorithm, Simulated Kalman Filter (SKF) had been proposed to solve image encryption problem. The objectives of the hybrid technique are to improve the security and add noise from the optimization algorithm and generate chaotic secret key. To achieve that, Lorenz chaotic system is implemented to this method and produce secret key sequence. SKF is one of the optimization methods that had been proved to have great performance in engineering applications from prediction, measurement, and estimation process. Thus, the proposed method is outperformed the results and analysis compared to literature as benchmarks. In short, the proposed hybrid approach is agile and efficient to apply in image encryption problem